Organ-on-a-chip: current gaps and future directions. (29th April 2022) - Candarlioglu, Pelin L.; Dal Negro, Gianni; Hughes, David; Balkwill, Frances; Harris, Kate; Screen, Hazel; Morgan, Hywel; David, Rhiannon; Beken, Sonja; Guenat, Olivier; Rowan, Wendy; Amour, Augustin
Abstract : As an emerging hot topic of the last decade, Organ on Chip (OoC) is a new technology that is attracting interest from both basic and translational scientists. The Biochemical Society, with its mission of supporting the advancement of science, with addressing grand challenges that have societal impact, has included OoC into their agenda to review the current state of the art, bottlenecks and future directions. This conference brought together representatives of the main stakeholders in the OoC field including academics, end-users, regulators and technology developers to discuss and identify requirements for this new technology to deliver on par with the expectations and the key challenges and gaps that still need to be addressed to achieve robust human-relevant tools, able to positively impact decision making in the pharmaceutical industry and reduce overreliance on poorly predictive animal models.